Evaluation of intraaneurysmal blood velocity by time-density curve analysis and digital subtraction angiography. - Tenjin, H; Asakura, F; Nakahara, Y; Matsumoto, K; Matsuo, T; Urano, F; Ueda, S (American Journal of Neuroradiology, 1998)
PURPOSE Our purpose was to evaluate intraaneurysmal blood velocity by using time-density curve analysis and digital subtraction angiography.METHODS In 31 aneurysms, aneurysmal blood velocity was examined with digital subtraction angiography to determine mean transit time (MTF), peak density time (time to peak opacification) (PDT), and time to half-peak opacification (T1/2). Thirty frames per second were acquired, and the time-density curve was calculated. Regions of interest were drawn on the proximal parent artery, on the distal parent artery, and on the aneurysm itself.RESULTS There was no significant difference in MTT of blood velocity in the proximal site on the parent artery, in the distal site on the parent artery, and in the aneurysm. Similarly, there was no significant difference in PDT in the parent artery, in the distal site on the parent artery, and in the aneurysm; nor was there a significant difference in T1/2 in the parent artery, in the distal site on the parent artery, and in the aneurysm; that is, intraaneurysmal blood velocity was similar to that in the parent artery. PDT and T1/2 of small aneurysms were faster than that of large aneurysms; that is, blood velocity of small aneurysms was faster than that of large aneurysms.CONCLUSION Intraaneurysmal blood velocity in small aneurysms is similar to that in the parent artery; consequently, the central stream probably reaches the aneurysmal wall. Intraaneurysmal blood velocity in large aneurysms appears to be somewhat slower than that in small aneurysms.